Maternal intention to exclusively breast feed among mainland Chinese mothers: A cross-sectional study. (February 2018) - Yang, Xiao; Ip, Wan-Yim; Gao, Ling-ling
Abstract: Objective: to examine postpartum maternal recall of their intentions to exclusively breast feed among breastfeeding women and identify its predictors. Design and setting: a cross-sectional descriptive study was conducted in a regional teaching hospital at Guangzhou, China between April 1 and July 14, 2014. Participants: 571 mothers who were within four days after delivery were recruited to the study. Measurements: data were collected by four research assistants with maternal intention to breast feed data sheet, the Network Support for Breastfeeding Scale (NSBS), and a socio-demographic data sheet. Findings: greater than half of the mothers (69.5%) intended to exclusively breast feed. The logistic regression analysis revealed six variables which predicted postpartum maternal recall of their intentions to exclusively breast feed. They were support from husband, being breast-fed as an infant, previous breast feeding experience, attending antenatal breast feeding class, time of decision to breast feed, and the rating of the importance of my baby's health. Conclusion and implications for practice: health care professionals could develop strategies to enhance mothers' intention to exclusively breast feed, such as providing antenatal breast feeding class on internet, a strong focus on the benefits of exclusive breast feeding on the baby's health in the education programme, and more efforts directed toward educating school-aged children and adolescents to modify societal perceptions of what are considered normal infant feeding. Mothers' husband could be encouraged in supporting exclusive breast feeding. Highlights: Rating of the importance of my baby's health was a predictor of maternal intention to exclusively breast feed. Attending the antenatal breast feeding class was a predictor of maternal intention to exclusively breast feed. Time of decision to breast feed was a predictor of intention to exclusively breast feed.